PENGARUH LINGKUNGAN SEKOLAH TERHADAP KARAKTER SISWA DI SDN 04 LIMBOTO - Rahmatia, Nursyakinah; Munirah, Munirah; Akolo, Ingka Rizkiyani (Jurnal As Sibyan, 2024)
This research aims to evaluate the extent to which the school environment influences student character development at SDN 04 Limboto. A quantitative approach utilizing survey methodology was employed to gather comprehensive and thorough information about how the school environment shapes student character at this institution. The study focused on SDN 04 Limboto's student population, drawing from a sample of 72 students. Questionnaires were utilized for data collection, followed by simple linear regression analysis. The findings revealed that the school environment significantly impacts student character formation, with environmental factors accounting for 64% of the influence and showing a 25.3% correlation. Analysis yielded the regression equation Y= 29.050 + 0.217(x), indicating that each enhancement in the school environment contributes to a 0.217 improvement in student character at SDN 04 Limboto. Given these significant findings regarding the school environment's influence on student character development, the study suggests that maintaining and improving the school environment would positively affect student character formation at SDN 04 Limboto.